Memahami Komunikasi Bisnis : Strategi Dan Pengelolaannya - Lisa Ramahdani; Halimah Helmi; Khairunnisak Nasution; Mustafaruddin Mustafaruddin; Suhairi Suhairi (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2022)
The communication strategy is an important thing in the communication process, where the communication strategy is carried out to make a communication successful so that the message or information can be conveyed according to its purpose. This study aims to analyze communication strategies in the business world. Using a normative legal approach with literature studies. Conduct library research with data sourced from related books, articles, journals and websites. Based on the results of the study, it was found that the communication strategy is very important and very influential in communicating to achieve the goals of the communication.